Eukoenenia mocororo (Palpigradi: Eukoeneniidae): a new troglobitic palpigrade from a Brazilian ferruginous cave - Souza, Maysa Fernanda Villela Rezende; Ferreira, Rodrigo Lopes (Zootaxa, 2022)
A new troglobitic palpigrade from Southeastern Brazil is described based on nine specimens (including males, females and immatures of all stages) collected in an iron ore cave named “Mocororô”. The most peculiar trait of Eukoenenia mocororo sp. nov. that readily distinguishes it from other Eukoenenia species described worldwide is the presence of fourteen pairs of setae (including the fusules) on first lobe of male genitalia. Although other palpigrades have been reported from Brazilian iron ore caves, this record is remarkable because Mocororô cave is inserted in Peixe Bravo River Valley (Northern Minas Gerais state)—a ferruginous system with dozens of caves that have been targeted for biospeleological studies only a few times. Therefore, the description of this new species, besides contributing to the conservation of Mocororô cave, constitutes an example of the high potential for discoveries in this region.